Cultural intermediaries in place branding: Who are they and how do they construct legitimacy for their work and for themselves?. (June 2018) - Warren, Giannina; Dinnie, Keith
Abstract: This article applies a social constructionist approach to the analysis of the promotional actors in place branding. Previous studies have provided useful conceptual and empirical perspectives on place branding as an emerging practice in urban governance. However, little attention has been paid to the dispositions and occupational resources drawn upon by the promotional actors responsible for the design and implementation of place brand strategies. This article extends Bourdieu's notion of cultural intermediaries to the field of place branding by analysing the promotional actors engaged in it. Through in-depth interviews with 16 professionals in Toronto, Canada, this paper employs a case study approach to identify the habitus, forms of social and cultural capital and field adaptation utilised by various promotional actors to not only construct legitimacy for their work for the city they represent, but also for themselves. Highlights: Promotional practitioners act as cultural intermediaries in place branding. They leverage forms of capital to create legitimacy for their work and themselves. Symbolic power is derived from occupational tools of social and cultural capital. This taste-making function informs social processes of tourism and urban planning.